Effectiveness and safety of traditional Chinese therapies intreating patients with amyotrophic lateral sclerosis: a protocol for systematic review and meta-analysis - Li, Rui; Bao, Tingting; Li, Bei; Xia, Peng; Zhang, Tingting; Zhang, Haoli; Huang, Fei (Frontiers in Neurology, 2024)
BackgroundAmyotrophic lateral sclerosis (ALS) is a chronic, progressive disease that affects both upper and lower motor neurons. Some physicians have used traditional Chinese therapies (TCT) to treat ALS. However, there has been no systematic review or meta-analysis to evaluate the effectiveness and safety of TCT interventions. This review aims to analyze the effects of TCT interventions for patients with amyotrophic lateral sclerosis.Methods and analysisThis study will include randomized, non-randomized, and quasi-experimental clinical trials, with participants being any age Amyotrophic Lateral Sclerosis (ALS) patients who have undergone TCT treatment. Two researchers will independently search databases including CENTRAL, PubMed, PEDro, EMBASE, CNKI, CBM, and SPORTDiscus, without restrictions on language or publication date. These researchers will independently screen titles and abstracts and extract data from the included studies. If deemed suitable for meta-analysis, data synthesis will be conducted using Review Manager V.5.3 software; any discrepancies will be resolved by a third researcher. The meta-analysis will compare the effects of TCT with placebo or other interventions. The main endpoint evaluated was the decrease in the overall score of the Amyotrophic Lateral Sclerosis Functional Rating Scale-Revised (ALSFRS-R; scoring from 0 to 48, where higher scores denote greater functionality) over a period of 24 weeks. Additional endpoints included the reduction rates in isometric muscle power, levels of phosphorylated axonal neurofilament H subunits in plasma, and slow vital capacity measurements. Furthermore, the study monitored the duration until occurrence of death, tracheostomy, or the need for long-term ventilation, as well as the time until death, tracheostomy, long-term ventilation, or hospital admission.Ethics and disseminationThroughout the entire process of this systematic review, no personal information was used, hence ethical review is not required. The results of this meta-analysis will be disseminated through publication in peer-reviewed journals and/or conference presentations.